2019
DOI: 10.1016/j.ejso.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic detection of sentinel lymph node in papillary thyroid carcinoma: The MAGIC-PAT study results

Abstract: Introduction: Despite the controversy concerning sentinel lymph node biopsy (SLNB) in papillary thyroid carcinoma (PTC), successful detection rates can be achieved by radioguidance and vital dyeing. However, the drawbacks in both techniques are notable. Magnetic-guided SLNB (mSLNB) using superparamagnetic iron oxide (SPIO) nanoparticles is appealing as an alternative procedure. Materials and Methods: mSLNB using the Sentimag-Sienna System ® , total thyroidectomy and central compartment dissection (CCD) were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Our analyses revealed high accordance between nomogram-based predictions and LNI rates in both sPLND techniques. These results suggest that magnetometer-guided sPLND is a reliable and promising alternative that can be used in PCa to overcome the disadvantages of radioisotope marking [ 26 , 27 ], as observed in other tumor entities [ 26 , 28 , 42 , 43 , 44 , 45 ]. Furthermore, an improved flow of the magnetic tracer may lead to an increased number of detected SLNs in magnetometer-guided sPLND, as observed in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Our analyses revealed high accordance between nomogram-based predictions and LNI rates in both sPLND techniques. These results suggest that magnetometer-guided sPLND is a reliable and promising alternative that can be used in PCa to overcome the disadvantages of radioisotope marking [ 26 , 27 ], as observed in other tumor entities [ 26 , 28 , 42 , 43 , 44 , 45 ]. Furthermore, an improved flow of the magnetic tracer may lead to an increased number of detected SLNs in magnetometer-guided sPLND, as observed in the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Using this method, the Spanish surgeons detected a median number of two sentinel nodes/patient, while the ratio of metastatic nodes was of 31%; among the retrieved non-sentinel nodes, the ratio of positive nodes was 10.2%, all cases of positive non-sentinel nodes being found among patients with positive sentinel nodes. Therefore, the authors demonstrated that the sensitivity of the method was 100%, the specificity was 81.8%, while the accuracy was 87.5%, underlining in this way the effectiveness of the method (18).…”
Section: Techniques Of Sentinel Node Detection In Thyroid Cancer Patimentioning
confidence: 87%
“…A more recent study conducted by Fustegueras et al (18) on 20 patients with papillary thyroid carcinoma demonstrated the utility of magnetic guided sentinel node biopsy using superparamagnetic iron oxide, a tracer which has been used in the last two decades as an intravenous contrast agent for magnetic resonance imaging studies (19). Using this method, the Spanish surgeons detected a median number of two sentinel nodes/patient, while the ratio of metastatic nodes was of 31%; among the retrieved non-sentinel nodes, the ratio of positive nodes was 10.2%, all cases of positive non-sentinel nodes being found among patients with positive sentinel nodes.…”
Section: Techniques Of Sentinel Node Detection In Thyroid Cancer Patimentioning
confidence: 97%
“…A magnetic SLNB is proposed as an alternative for a radioactive SLNB in, e.g., breast cancer [10,11], prostate cancer [12], and, more recently, for thyroid carcinoma [13] and oral cancer [14,15]. The magnetic SLNB utilizes a magnetic tracer (superparamagnetic iron oxide (SPIO) nanoparticles) and a magnetometer.…”
Section: Introductionmentioning
confidence: 99%
“…Injected tracer can be used for preoperative SPIO-enhanced magnetic resonance imaging (MRI) to visualize and identify the location of LNs with iron uptake [16,17]. Simultaneously, SPIOs are also used for intraoperative detection of SLNs by a magnetometer [10][11][12][13][14][15]. What should be considered is the difference in SPIO-sensitivity between MRI and the magnetometer [18].…”
Section: Introductionmentioning
confidence: 99%